2005
DOI: 10.1111/j.1365-2559.2005.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive (intracapsular) carcinoma ex pleomorphic adenoma: recognition of focal carcinoma by HER‐2/neu and MIB1 immunohistochemistry

Abstract: The current data suggest that non-invasive carcinoma ex PA is a genuine carcinoma within a PA. However, the presence of cyto-nuclear atypia is not sufficient to make a definite diagnosis of malignant change, which requires a combination of morphology and immunohistochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 23 publications
(21 reference statements)
10
85
3
3
Order By: Relevance
“…Immunohistochemical staining of C-erbB-2 protein was found to be higher (21%) in cell membranes of high grade Ca ex PA [49]. Rosa et al [49] also found negative C-erbB-2 protein expression in low grade Ca ex PA, as did Di Palma et al [22] in their study of 11 Ca ex PA cases. These findings indicate that C-erbB-2 may play a role in tumour progression and malignant transformation of Ca ex PA. Anti-C-erbB-2 therapy (Herceptin) has been successfully used to control a case of advanced Ca ex PA.…”
Section: Growth Factors and Receptorsmentioning
confidence: 90%
See 1 more Smart Citation
“…Immunohistochemical staining of C-erbB-2 protein was found to be higher (21%) in cell membranes of high grade Ca ex PA [49]. Rosa et al [49] also found negative C-erbB-2 protein expression in low grade Ca ex PA, as did Di Palma et al [22] in their study of 11 Ca ex PA cases. These findings indicate that C-erbB-2 may play a role in tumour progression and malignant transformation of Ca ex PA. Anti-C-erbB-2 therapy (Herceptin) has been successfully used to control a case of advanced Ca ex PA.…”
Section: Growth Factors and Receptorsmentioning
confidence: 90%
“…It is also known in the literature as intracapsular CA ex PA and carcinoma in situ [21,22]. The carcinoma component in a non-invasive Ca ex PA is confined within the well-defined fibrous capsule of the PA.…”
Section: Microscopicmentioning
confidence: 99%
“…The gain of genes or chromosome regions commonly occurs in tumour cells, but a recent study using FISH did not show evidence of HER-2 gene amplification in benign pleomorphic adenomas (30). Nonetheless, HER-2 amplification has been previously indicated as a common event in the process of PA transformation into carcinoma ex pleomorphic adenoma (10). It has also been shown that HER-2 and TP53 are synergistically involved in the early stages of malignant transformation of PA (25,31).…”
Section: Discussionmentioning
confidence: 99%
“…It is also functionally related to HER-2 and H-ras. To date, little is known about the involvement of HER-2/H-ras/c-myc signalling cascade in the development of PAs and about its possible prognostic significance in both PAs and CXPAs (10,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…HER-2/neu is a useful marker in the differential diagnosis of pleomorphic adenoma versus noninvasive carcinoma ex pleomorphic adenoma. This is especially true when there a suspicion that the pleomorphic adenoma includes a malignant component or shows malignant transformation 7 . Recent studies have revealed that the androgen receptor AR , Ki-67, and p53 may also be useful markers for this differential diagnosis, although they were not examined in this study.…”
Section: Discussionmentioning
confidence: 99%